2022
DOI: 10.1371/journal.pone.0276990
|View full text |Cite
|
Sign up to set email alerts
|

AGR2 expression as a predictive biomarker for therapy response in esophageal squamous cell carcinoma

Abstract: Despite multidisciplinary therapy, the prognosis is poor for esophageal squamous cell carcinoma (ESCC). In the locally advanced stage, neoadjuvant chemoradiotherapy (nCRT) followed by surgery could provide survival benefits to some patients. Here, we aimed to identify for tumor therapy response a biomarker based on RNA sequencing. We collected endoscopic biopsies of 32 ESCC patients, who were divided according to nCRT response, into two groups: the complete response group (n  =  13) and the non-complete respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Beyond these ndings, we have also demonstrated subtle transcriptomic differences among T cell subpopulations when stratifying patients according to disease response to neoadjuvant therapy. Previous studies have explored the prognostic bene t of AGR2 with upregulation being associated with poorer oncological outcomes in patients with squamous cell carcinoma of the esophagus 45 . This outcome is thought to be due to AGR2 interaction with disulphide-dependant complexes including MUC-5 that in turn promotes tumoral proliferation and cell migration in adenocarcinoma 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Beyond these ndings, we have also demonstrated subtle transcriptomic differences among T cell subpopulations when stratifying patients according to disease response to neoadjuvant therapy. Previous studies have explored the prognostic bene t of AGR2 with upregulation being associated with poorer oncological outcomes in patients with squamous cell carcinoma of the esophagus 45 . This outcome is thought to be due to AGR2 interaction with disulphide-dependant complexes including MUC-5 that in turn promotes tumoral proliferation and cell migration in adenocarcinoma 46 .…”
Section: Discussionmentioning
confidence: 99%
“…And subsequent studies demonstrated its role in promoting tumor progression in cancer cells associated with sex hormone receptors [71,86]. Further research has confirmed that AGR2 can be overexpressed and exert pro-cancer functions in various solid cancers [24], ranging from adenocarcinomas to squamous carcinomas, including breast adenocarcinomas [87], pancreatic adenocarcinomas [88], esophageal adenocarcinomas [89], prostate adenocarcinomas [78], esophageal squamous cell carcinomas [90], and HCC [12].…”
Section: Association Between Agr2 and Hepatobiliary And Pancreatic Ca...mentioning
confidence: 92%
“…AGR2 has consistently emerged as a potential therapeutic target in colon cancer from various perspectives [15,126,143]. AGR2 is overexpressed in esophageal squamous cell carcinoma and that AGR2 expression may serve as a biomarker for predicting the response to treatment in esophageal squamous cell carcinoma and as a potential therapeutic target for patients with P53 wild-type esophageal squamous cell carcinoma [90,144]. Targeting the link between ovarian cancer [145], esophageal squamous cell carcinoma [90], and other cancers with AGR2 immunity, we can hypothesize that AGR2 influences the immune microenvironment of patients, suggesting a potential undiscovered link between the two that may impact patient prognosis.…”
Section: Agr2 and Clinical Treatmentmentioning
confidence: 99%
“…AGR2 performs the function of the molecular chaperone, which regulates the folding, trafficking, and assembly of cysteine-rich transmembrane receptors. It was also implicated in inflammation and cancer progression and in the regulation of the cell migration and transformation [139] by suppressing tumor inhibitor p53 [140]. The NACA gene was shown in the list of down-regulated genes at 7 days of RPE reprogramming.…”
Section: Proteins With a Chaperone Functionmentioning
confidence: 99%